Predictors of treatment outcome in higher levels of care among a large sample of adolescents with heterogeneous eating disorders - Erin E. Reilly; Sasha Gorrell; Alan Duffy; Dan V. Blalock; Philip Mehler; Harry Brandt; Susan McClanahan; Kianna Zucker; Naomi Lynch; Simar Singh; Catherine R. Drury; Daniel Le Grange; et al. (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Despite widespread use of higher levels of care in treating eating disorders in adolescents, research supporting the use of these treatments remains limited by small sample sizes and a predominant focus on anorexia nervosa. Further, existing data regarding predictors of outcome have yielded mixed findings. In the current study, we evaluated treatment outcomes and predictors of outcome among a large sample of adolescents with eating disorders presenting to inpatient, residential, partial hospitalization programs, and intensive outpatient programs across the United States. Methods Adolescents (N = 1,971) completed self-report measures of eating disorder symptoms, depression, and anxiety at treatment admission, stepdown, and discharge. Using linear mixed effect models, we evaluated changes in symptoms over treatment separately among youth admitted to inpatient/residential treatment and those admitted to partial hospitalization/intensive outpatient programs, and used established metrics to gauge frequency of reliable (i.e., statistically reliable) and clinically significant change. Results Results suggested decreases in eating disorder symptoms, depression, and anxiety from intake to discharge. Around 50% of the sample reported reliable decreases in eating disorder symptoms at stepdown and discharge, with 30% of the sample reporting reliable reductions in depression and anxiety. Psychiatric comorbidity, primary diagnosis, age, and eating disorder symptoms at admission consistently predicted treatment-related change, although patterns in findings varied across symptoms. Conclusions Data from our sample are consistent with past work suggesting that adolescents enrolled in higher levels of care report clinical benefit; however, these effects are heterogenous, and a significant portion of individuals may not report reliable change in symptoms. Ultimately, ongoing work is required to better understand how and for whom higher levels of care may achieve their benefit and to identify the optimal approach for improving outcomes for adolescents with eating disorders.